Design of a Digital Portal for Village Small and Medium Enterprises as Implementation fo a Business Communication Model for Developing Online Marketing and Sales Strategies of Micro Small and Medium Enterprises and Tourism Product in Cimacan Village (ABDIMAS: Jurnal Pengabdian Masyarakat, 2024)
Currently there are approx 60 million micro, small and medium enterprises in Indonesia. The role of small and medium enterprises is very important for the Indonesian economy because they are able to contribute more than Rp. 8,500 trillion in gross domestic receipts or 57.8 percent. There are 64 million small and medium enterprise business units recorded and capable of absorbing 116 million workers or 97 percent of the national workforce. However, various problems and challenges are faced by micro and small businesses to develop their businesses, especially in digital marketing, packaging and improving product quality. Therefore, Putra Indonesia University carries out community service activities, namely small and medium business owners in developing their products. The methods used in this community service activity include: 1) Identification of Community Needs; 2) designing marketing applicationsmobile, Inebsite profile small and medium businesses, strategypersonal branding, sales onecommerce, strengthening promotions through social media,workshop promotional content andmaintenance; 3) Training regarding promotional content, use of marketing applicationsmobile, website, in-depthpersonal branding, usee- commerce,and promotion on social media; 4) mentoring; 5) program implementation; 5) program evaluation; and 6) hosting the Cimacan BUMDes small and medium enterprise digital portal website in Cimacan www.pkm-bumdescimacan.com. Expected benefit indicators: 1) Increase in turnover and assets; 2) Have the right entrepreneurial mindset in growing/developing your business; 3) Increased knowledge and skills in utilizing digital promotional and marketing media; 4) Digitizing business using technology; 5) The product is accepted by the market; 6) Product innovation; 7) Be competitive.